2020
DOI: 10.2139/ssrn.3569554
|View full text |Cite
|
Sign up to set email alerts
|

The Macroeconomic Spillover Effects of the Pandemic on the Global Economy

Abstract: The macroeconomic spillover effects of the pandemic on the global economy Key takeaways •Given the historical persistence of economic activity, the reduction of GDP due to confinement measures is likely to drag on over several quarters. The total GDP shortfall could be as much as twice that implied by the direct initial effects of confinement.• This persistence reflects in part two types of spillovers across countries. One is due to the risk that uncoordinated confinements lead to repeated virus outbreaks and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 0 publications
0
46
0
2
Order By: Relevance
“…This study complements this work by quantifying the short-term implications of the pandemic on job losses and business closures and shows that these impacts further aggravate inequality in the region. Furthermore, [22] describes how macroeconomic spillovers can amplify the adverse economic effects of the pandemic, which would suggest that the estimates obtained are a lower bound. The results presented in this study may be useful to inform pandemic mitigation policy; by indicating where the economic impacts of large-scale lockdowns are particularly large [23].…”
Section: Introductionmentioning
confidence: 99%
“…This study complements this work by quantifying the short-term implications of the pandemic on job losses and business closures and shows that these impacts further aggravate inequality in the region. Furthermore, [22] describes how macroeconomic spillovers can amplify the adverse economic effects of the pandemic, which would suggest that the estimates obtained are a lower bound. The results presented in this study may be useful to inform pandemic mitigation policy; by indicating where the economic impacts of large-scale lockdowns are particularly large [23].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the pandemic is analysed in the context of the global economy. In their work, Kohlscheen et al (2020) present estimates of the negative impact of the pandemic on GDP in selected economic areas of the world, assuming one or two waves of this phenomenon. They also suggest coordinating macroeconomic policies internationally to make them more effective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study also concluded that US uncertainty shocks again reduce the output and consumer prices while increasing net exports. Kohlscheen et al (2020) discussed the spillover effects of the COVID-19 pandemic on the global economy. Bayesian vector autoregression (BVAR) model was applied in this study, which concluded that the spillover effects across the big economic blocs are large.…”
Section: Literature Reviewmentioning
confidence: 99%